Meningkatkan Partisipasi dan Dampak Positif Kegiatan Donor Darah Di Kota Bandung - Umban Adi Jaya; Herni Herdiani; Riani Winarni; Rizki Chrisulianti; Bambang Somantri (LPPM Universitas HKBP Nommensen, 2025)
Blood donation activities play an important role in ensuring the availability of blood for various medical needs, both for surgery, accidents, and dengue fever cases. Through this community service activity, the Community Service Team of the Indonesian Science University in collaboration with the Indonesian Red Cross (PMI) of Bandung City held a blood donation activity at H&H Cafe, Bandung, on February 8, 2025. The main objective of this activity is to increase public awareness of the importance of blood donation, introduce the application of strategic management in social activities, and increase community participation in blood donation. This activity managed to collect 63 blood bags, exceeding the initial target of 50 bags. The success factors of this activity include effective promotion through social media, efficient resource management, and clear target setting. The principle of strategic management was applied to optimize the planning, implementation, and evaluation of activities, so that they can achieve long-term success. Despite facing obstacles such as limited space and lack of volunteers, solutions such as donor scheduling and additional volunteers managed to overcome these obstacles. This activity not only meets the need for blood in Bandung City, but also increases public awareness of the benefits of regular blood donation. Recommendations for the future are to carry out blood donation activities routinely with a broader strategic management approach to increase efficiency and participation.